Determinan Penggunaan Sistem Informasi Akuntansi pada Usaha Mikro, Kecil, dan Menengah (UMKM) di Kota Surakarta - Damayanti, Stefani; Eddy Sarwono, Aris (PENG: Jurnal Ekonomi dan Manajemen, 2025)
The rapid evolution of information technology has drastically changed the landscape of accounting information systems. This study aims to measure how much influence the perception of ease, benefits, and understanding of accounting on the application of accounting information systems. Thus, business people need to be adaptive to the latest developments in information technology. Specifically, this study wants to identify how much influence the perceived ease of use, perceived benefits, and the level of employee accounting knowledge have on the adoption of cloud-based accounting information systems in improving business process efficiency. This type of research is quantitative research. The population in this study were culinary MSME owners in 2023 with a total of 5,536 business actors. The sampling technique used purposive sampling of 106 respondents. The data collection technique is using a questionnaire. The application used to help complete the proposed data analysis uses SPSS 25. This study uses data analysis techniques in the form of multiple linear analysis and moderated regression analysis (MRA) tests. The results showed that perceived convenience had no significant effect on the use of AIS, while perceived usefulness and accounting knowledge had a significant effect on the use of AIS on MSME owners in Surakarta City. MRA results show that accounting training is not able to moderate the effect of perceived usefulness and accounting knowledge on the use of AIS.